Integrated fuzzy-PI controlled current source converter based D-STATCOM. Issue 1 (31st December 2016) - Deben Singh, M.; Mehta, Ram Krishna; Singh, Arvind Kumar
Abstract: The distribution static synchronous compensator (D-STATCOM) is a shunt-connected current injection custom power (CP) device that can be used for improving quality and reliability of the power supplied to electric consumers under dynamic conditions of the distribution system. The CP devices such as dynamic voltage restorer and unified power quality conditioner including D-STATCOM are mostly designed and implemented using voltage source converter topology. The performance of D-STATCOM can be improved, if it is realized by using a current source converter topology which can generate a controllable current directly at its output terminals. Although the current source converter (CSC) topology offers many promising advantageous features, not much research publications with CSC-based approach in the field of CP devices has been reported over the last one decade. This paper presents a novel method of realizing a D-STATCOM using CSC topology with an integrated fuzzy-PI controller for not only mitigating voltage sag but also capable of maintaining improved DC-link voltage profile. The model has been simulated in the MATLAB/SIMULINK environment. The simulation results under steady state and dynamic load perturbation provide excellent output characteristics that support the validity of the proposed model.